Pengaruh Kompensasi, Lingkungan Kerja dan Motivasi Terhadap Kinerja Pada PT. Tonga Tiur Putra Pandangan Kabupaten Rembang. - Nurhidayati, Anik (STIE YPPI Rembang, 2008)
The study aims to examine the effect of compensation, work environment and motivation on performance in PT. Son of Tonga Tiur view Rembang. The sample in this study amounted to 75 respondents. The first hypothesis with the value t count> t table (2.115> 2.000) with significance level 0.038 <0.05, means that there is significant influence of com- pensation (X1) to employee performance (Y). Testing the second hypothesis is the work environment variables (X2 ) to employee performance (Y) can know the results of the calculations whereas the t 3.818 2.000 t table at the 0.05 sig- nificance level (? = 0.05). Thus the significant effect of work environment (X2) on employee performance (Y). The third hypothesis tests the motivation variable (X3) on employee performance (Y) can be detected t count is greater than t 2.058 2.000 table, at the level of significance is 0.05 ( ? = 0.05), thus there is significant influence of motivation (X3) on employee performance (Y). Hypothesis test kempat com- pensation variable (X1) working environment (X2) and moti- vation (X3) jointly affect the performance of the employee (Y). Regression calculation is obtained f count> f table (12.765> 2.74) at 0.05 significance level> 0.00. Thus the three variables (X1, X2, X3) jointly have a significant influence on employee performance (as Y). Adjusted R2 value (coeffi- cient of determination) indicates the variable compensation, work environment and motivation can explain the influence of 32.3% on performance, while the rest equal to 67.7% ex- plained by other factors not included in this study.Keyword: compensation, work environment, motivation, per- formance